Ne plus avoir le temps, ou le risque de l’errance temporelle : considérations anthropologiques et éducatives - Géraldine Potier; Renaud Hétier (Recherches en Éducation)
This contribution aims at proposing a phenomenological perspective on wandering from an alternative point of view, since it is about temporal wandering. The modern individual is described as unbound, by the economic hold, by the distancing of the relation to the other, of the body itself and of the sensibility, on a background of anthropological tendency. This untying could be a freedom, but it deprives him above all of containment and support, and delivers him to a "raw" time, which passes without him, without him managing to inhabit it. This exposure to a liquid time particularly affects childhood, which finds itself, in the Anthropocene, in front of a threatening and unprecedented future, which the transmission of the past does not illuminate, which raises important educational questions.